Ensuring Quality in the OECD AI Lifecycle Through ISO/IEC Standards - Torres, Juan Ignacio (2025)
The integration of artificial intelligence (AI) technologies within organizations presents both significant opportunities and complex challenges. To manage this complexity, ISO/IEC standards provide a structured framework for the adoption and management of AI systems throughout their lifecycle. This article explores the role of ISO/IEC standards in ensuring the quality, security, and ethical alignment of AI systems, based on the lifecycle framework defined by the Organisation for Economic Co-operation and Development (OECD). The paper outlines how these standards support AI system development, from planning and design through deployment and monitoring, addressing critical issues such as governance, data quality, bias detection, and system reliability. A comprehensive quality model is proposed, drawing on ISO/IEC 25058 and 25059 standards, to assess the effectiveness and transparency of AI systems in real-world environments. The adoption of these standards is shown to enhance corporate reputation, improve regulatory compliance, and mitigate risks, positioning organizations to leverage AI technologies responsibly and efficiently.